Photography, Life, and the Opposites - Bernstein, Len (Delia Press, 2013)
Photography, Life, and the Opposites, with a foreword by Robert Coles, is about what makes for beauty not only in Len Bernstein's chosen art, but in all the arts. And it is about life, and how art can teach us to live it. The author's critical approach is based on this historic principle stated by Eli Siegel, founder of Aesthetic Realism: All beauty is a making one of opposites, and the making one of opposites is what we are going after in ourselves. You will learn what makes a photograph successful and how our most everyday and urgent questions are answered in art. Questions that affect us all, including: What makes true love possible and keeps it from fading? How should we see the people close to us, including in a time of illness? What makes us cruel to others, and how can we change? The book is illustrated with over 70 of Mr. Bernstein's stirring photographs of daily life, many of which are in public collections in the US and abroad, as well as photographs by others. Together with the text, they are a means of understanding: What does it mean to have a beautiful way of seeing people and things; a way of seeing that will make us proud? And what stops us from having it?